Empirical study on co-movement of Hong Kong and ShenZhen stock markets. - Chan, Shek. (2011)
In recent years, the amount and types of foreign equity investments have increased enormously in many of the emerging financial markets of the Asia Pacific region. With continuing effort to modernize her economy, China has drawn increasing interest from foreign investors. Due to its geographical proximity to China, Hong Kong is one of the earliest and major foreign investors in China.